PENERAPAN E-MARKETING MENGGUNAKAN MODEL OOHDM DAN STRATEGI MARKETING 7P (STUDI KASUS : SUDDEN INC) - Anjar Sari (Jurnal Teknologi dan Sistem Informasi, 2022)
Abstract Sudden Inc. is a trading company engaged in fashion, supplies and distribution accessories that have implemented an offline marketing system or only in stores. The application of the system still has shortcomings such as a small market reach because customers who come only to the store environment, product introductions are only carried out at stores so that customers only know product specifications when shopping at stores and through individuals and telephone media so that the process of recording transaction data often results in errors. at the time of calculation, they have not implemented a good e-marketing system for customers, because there are no discounted prices, have not implemented an online sales transaction process and marketing has not implemented an e-marketing strategy.Based on the above background, the author makes a system for the distribution of Sudden Inc. to handle the problem of product introduction, product sales transaction processes, product promotion and service systems with additions such as chat. The system was built using the web, so that it is more easily accessed online by consumers, so that responses from respondents related to system development were obtained, namely the usability testing process obtained a score of 92.66% which can be concluded that students have been highly approved and based on functionality obtained a score of 84, 61% concluded that students have been accepted by users Keywords: The application E-Marketing,Model OOHDM, Marketing 7P.